Actinic lichen planus of unusual presentation - Mebazaa, Amel (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2010)
Actinic lichen planus (ALP) is a distinct variant of lichen planus mainly involving teenagers with an Asian racial profile. Three clinical types of ALP have been described: annular, pigmented, and dyschromic. We report an ALP withunusual presentation in a 56-year-old woman with no relevant medical history, which was clinically suggestive of actinic keratosis. Histological findings refined the diagnosis by showing typical aspects of lichen planus. This dermatosis, which is frequent in Tunisia because of sun exposure, may cause mainly aesthetic damage and requires adequate photoprotection.
Keywords: dermatologija; Fotosenzibilnost, motnje; kožne spremembe; Lichen Planus; Lihen planus; Middle Age; Photosensitivity Disorders; Srednja leta; Tunisia; Tunizija